2019
DOI: 10.48550/arxiv.1906.12034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Quadratic Gravity with Binary Inspirals

Abstract: In this paper, we study gravitational waves generated by binary systems within an extension of General Relativity which is described by the addition of quadratic in curvature tensor terms to the Einstein-Hilbert action. Treating quadratic gravity as an effective theory valid in the low energy/curvature regime, we argue that reliable calculations can be performed in the early inspiral phase, and furthermore, no flux of additional massive waves can be detected. We then compute massive dipole (-1PN), and Newtonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Given the constraints on parameters of quadratic gravity [23], we found that PBHs with even vanishing ADM mass can be stable. Furthermore, we argue that microlensing is less prominent for these black holes.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Given the constraints on parameters of quadratic gravity [23], we found that PBHs with even vanishing ADM mass can be stable. Furthermore, we argue that microlensing is less prominent for these black holes.…”
Section: Introductionmentioning
confidence: 94%
“…They cannot be calculated within the effective theory framework and must be extracted from observations. In [23] we obtained the following bounds on these parameters from the LIGO/Virgo gravitational wave data with the requirement of the absence of tachyonic instabilities:…”
Section: Static Spherically Symmetric Solutions In Quadratic Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dipole emission are present in the approach by Ref. [72] where PN correction to the R 2 -model are accounted for.…”
Section: A Energy-momentum Tensor and The Multipole Momentsmentioning
confidence: 99%